Attentional bias in eating disorders. - Shafran, R; Lee, M; Cooper, Z; Palmer, R; Fairburn, C (2007)
OBJECTIVE: To examine the relationship between eating disorders and attentional biases. METHOD: The first study comprised 23 female patients with clinical eating disorders, women with high levels of anxiety (n = 19), and three female normal control groups comprising low (n = 31), moderate (n = 21), or high levels of shape concern (n = 23). The second study comprised 82 women with clinical eating disorders and 44 healthy controls. All participants completed measures of eating disorder psychopathology and completed a modified pictorial dot-probe task. RESULTS: In the first study, biases were found for negative eating and neutral weight pictures, and for positive eating pictures in women with eating disorders; these biases were greater than those found in anxious and normal controls. The second study replicated these findings and biases were also found for negative and neutral shape stimuli. CONCLUSION: It is concluded that future research should establish whether such biases warrant specific therapeutic interventions.